CHARACTERIZATION OF THE ESSENTIAL OIL OF CLINOPODIUM REVOLUTUM AND COMPUTATIONAL STUDY OF ITS BIOACTIVE COMPOUNDS AGAINST CANCER - Valderrama Negrón, Ana (2023)
Cancer is one of the main causes of death worldwide. The search for bioactive compounds against cancer is enhanced by the use of computational tools and molecular databases. Clinopodium Revolutum (CR) is a plant used for medicinal purposes in various ailments; however, further scientific studies are needed to support its bioactivity. In this work, 55 components in the essential oil of CR are analyzed, identified by GC-MS, with potential anticancer activity through in silico studies. Anticancer drug receptors were selected, such as cyclin-dependent kinase 2 (CDK-2), cyclin-dependent kinase 6 (CDK-6), topoisomerase-I (Topo I), topoisomerase-II (Topo II), B-cell lymphoma 2 (Bcl-2), and vascular endothelial growth factor receptor 2 (VEGFR-2). All these structures were obtained from the Protein Data Bank RCSB. According to molecular docking simulations, it was found that perilaldehyde from the essential oil showed higher interaction affinity with the pharmacological targets CDK-2, CDK-6, Topo I, and VEGFR. Perilaldehyde-receptor complexes were simulated by molecular dynamics for 50 nanoseconds, identifying predominantly hydrophobic interactions and hydrogen bonds mediated by solvent water in their stabilization. Our findings demonstrate that the compounds in the essential oil of CR present potential anticancer activity.